P18-17 No Evidence of E-Cigarette Aerosol-Induced Cisplatin Resistance in Head and Neck Cancer Cells: Findings from the Replica International Study Group - G. Carota; R. Emma; K. Partsinevelos; S. Rust; A. Sun; A. Giordano; V. Volarevic; R. Lesmana; H. Goenawan; M.I. Barliana; A. Arsenijevic; N. Kastratovic; et al. (Toxicology Letters, 2025)

Large silicic magma bodies and very large magnitude explosive eruptions - R. S. J. Sparks; J. D. Blundy; K. V. Cashman; M. Jackson; A. Rust; C. J. N. Wilson (Bulletin of Volcanology, 2022)
Over the last 20 years, new concepts have emerged into understanding the processes that lead to build up to large silicic explosive eruptions based on integration of geophysical, geochemical, petrological, geochronological and dynamical modelling. Silicic melts are generated within magma systems extending throughout the crust by segregation from mushy zones. Segregated melt layers become unstable and can assemble into ephemeral upper crustal magma chambers rapidly prior to eruption. In the next 10 years, we can expect major advances in dynamical models as well as in analytical and geophysical methods, which need to be underpinned in field research.

Contrasting mechanisms of magma fragmentation during coeval magmatic and hydromagmatic activity: the Hverfjall Fires fissure eruption, Iceland - E. J. Liu; K. V. Cashman; A. C. Rust; A. Höskuldsson (Bulletin of Volcanology, 2017)

MeMoVolc consensual document: a review of cross-disciplinary approaches to characterizing small explosive magmatic eruptions - L. Gurioli; D. Andronico; P. Bachelery; H. Balcone-Boissard; J. Battaglia; G. Boudon; A. Burgisser; M. R. Burton; K. Cashman; S. Cichy; R. Cioni; A. Di Muro; et al. (Bulletin of Volcanology, 2015)

Evolution of crust- and core-dominated lava flows using scaling analysis - Angelo Castruccio; A. C. Rust; R. S. J. Sparks (Bulletin of Volcanology, 2013)

Multiphase petrography of volcanic rocks using element maps: a method applied to Mount St. Helens, 1980–2005 - D. D. Muir; J. D. Blundy; A. C. Rust (Bulletin of Volcanology, 2012)

Multiple origins of obsidian pyroclasts and implications for changes in the dynamics of the 1300 B.P. eruption of Newberry Volcano, USA - A. C. Rust; K. V. Cashman (Bulletin of Volcanology, 2007)

Mapping porosity variation in a welded pyroclastic deposit with signal and velocity patterns from ground-penetrating radar surveys - A. C. Rust; J. K. Russell (Bulletin of Volcanology, 2001)